Microfluidics-based fundamental characterization of external concentration polarization in forward osmosis - Jiao, Yanmei (2021)
External concentration polarization (ECP) refers to the local variation of solution concentration near a membrane surface in forward osmosis (FO). The existence of ECP leads to much lower solvent permeating flux, and hence ECP is a major factor deteriorating FO membrane performance. Therefore, understanding ECP is of practical importance to the control and optimization of FO processes. Previous characterizations of ECP, however, are largely based on indirect experiments by measuring FO permeating flux which together with a certain analytical model is used to infer the ECP characteristics. Here, we report a microfluidics-based characterization of ECP, allowing for directly visualizing the ECP layer under well-controlled conditions. The thickness of the ECP layer and the FO permeating flux are obtained under various rates of tangential flow along the FO membrane surface, which establish a direct evidence of ECP characteristics in the FO process. To interpret the experimental results, a numerical model based on convection–diffusion theory is formulated, and a reasonable agreement between the experiments and the numerical simulations is found. Expectedly, our microfluidics-based approach provides a viable and efficient way of characterizing concentration polarization in membrane systems.